An Analysis of the Effectiveness of the Implementation of Integrated Waste Management Policies in Banten Province in Supporting Sustainable Development - Alam, Alief Nazwa; Stiawati, Titi; Satriyadi, Satriyadi; Elsiana, Elsiana; Masduki, Masduki; Pambudi, Krishna (Indonesian Journal of Social Science Research, 2026)
Waste management is a strategic issue in sustainable development, particularly in Banten Province, which has experienced an increase in waste generation alongside population growth and economic activity. Based on data from the National Waste Management Information System, the volume of waste in this region shows an upward trend each year, while the level of waste management remains suboptimal. This study aims to analyze the effectiveness of the implementation of integrated waste management policies in Banten Province in supporting sustainable development. This study employs a descriptive qualitative approach with public policy analysis. Data were collected through literature reviews, official government documents, and secondary data related to waste generation and management. The analysis utilized a policy implementation model encompassing variables such as communication, resources, disposition, and bureaucratic structure. The results indicate that the effectiveness of policy implementation remains suboptimal, as evidenced by low rates of waste reduction at the source (less than 30%), limited waste processing facilities and infrastructure, and uneven application of the 3R concept (Reduce, Reuse, Recycle). Furthermore, coordination among stakeholders remains weak and public participation is relatively low, resulting in the majority of waste still ending up at Final Disposal Sites (FDS) via landfill methods. The study’s conclusion emphasizes the need for institutional capacity building, increased investment in waste processing infrastructure and technology, and sustainable public education strategies to enhance policy effectiveness and support sustainable development in Banten Province.